2020
DOI: 10.5650/jos.ess19202
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lipase Purified from <i>Aspergillus fumigatus</i> in the Syntheses of Ethyl Acetate and Ethyl Lactate

Abstract: Introduction Lipases triacylglycerol ester hydrolases E.C. 3.1.1.3 are ubiquitous enzymes that catalyse the breakdown of fats and oils with subsequent release of free fatty acid, diacylglycerol, monoacylglycerol and glycerol 1 4. They are found in animals, plants, fungi and bacteria and are of considerable physiological significance and industrial potential 5. However, the most suitable sources for lipase production are the microorganisms which can produce high quality lipases in lower cost and shorter time 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The lactic acid concentration decreased from 7.15 ± 0.03g/100g to 6.33 ± 0.03g/100g dry weight during the aging stage. The esterification reaction occurred during the aging stage, which may be the reason for the decrease in the lactic acid concentration ( Mehta et al, 2020 ). The acetic acid content first increased and then decreased with fermentation duration, and reached 8.69 ± 0.07g/100g dry weight on the 11th day.…”
Section: Resultsmentioning
confidence: 99%
“…The lactic acid concentration decreased from 7.15 ± 0.03g/100g to 6.33 ± 0.03g/100g dry weight during the aging stage. The esterification reaction occurred during the aging stage, which may be the reason for the decrease in the lactic acid concentration ( Mehta et al, 2020 ). The acetic acid content first increased and then decreased with fermentation duration, and reached 8.69 ± 0.07g/100g dry weight on the 11th day.…”
Section: Resultsmentioning
confidence: 99%
“…Ethyl acetate, a short-chain ester, is a flavor compound with a fruity and solvent-like aroma. Previous studies demonstrated that lipase-catalyzed esterification of acetic acid with ethanol yielded ethyl acetate as the main product 105 . In addition, various yeasts can also esterify acyl-CoA with ethanol to form ethyl acetate through alcohol acetyltransferases 106 .…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Mehta et al (2020) reported that the esterification of ethanol and acetic acid produces ethyl acetate, while the esterification of ethanol and lactic acid gives ethyl lactate; both reactions are catalyzed by the lipase of Aspergillus fumigatus.…”
Section: In Medical and Pharmaceutical Applicationsmentioning
confidence: 99%